Linking organizational and individual factors to Government-to-Business system performance - Hussin, Husnayati; Kassim, Erne Suzila (Design for Scientific Renaissance, 2011)
In an attempt to deliver better service performance and improve the interactions, a large number of public agencies have taken the steps to transform their conventional business activities to online system known as government-to-business (G2B) system. Hence, the reformation of the business process has led to the evaluation of the system service performance and investigation of the factors that shape the success of the G2B implementation. Therefore, we attempt to evaluate the G2B service performance and examine the linkage of organizational and individual factors to the performance. Findings of the study show organizational learning and user attitude of organizational and individual factors respectively play a major role is determining the G2B system use. In addition, the use of IS in the interaction between government agencies and business entities has significant influence on the service performance, measured as transparency, service quality and information quality. The findings provide a new perspective for public agencies in their future e-government implementation.